Potential roles of myosin VI in cell motility. (21st September 2009) - Chibalina, Margarita V.; Puri, Claudia; Kendrick-Jones, John; Buss, Folma
Abstract : There is now increasing evidence that myosin motor proteins, together with the dynamic actin filament machinery and associated adhesion proteins, play crucial roles in the events leading to motility at the leading edge of migrating cells. Myosins exist as a large superfamily of diverse ATP-dependent motors, and in the present review, we focus on the unique minus-end-directed myosin VI, briefly discussing its potential functions in cell motility.